From reindeer to rhino : reflections on ‘Climate change mitigation and adaptation benefits of wilder rangelands’ - Kerley, Graham I.H.; Cromsigt, Joris P.M.G. (South African Journal of Science, 2020)
Ever since the Swedish botanist Anders Sparrman1 commented in 1786 on the state of overgrazing brought about by sedentary trekboer pastoralists in the southwestern Cape, the optimal use of rangelands in South Africa has been the subject of debate. Two centuries later, Hoffman and Ashwell2 painted a bleak picture of our stewardship of this precious resource. These rangelands are not merely a source of fibre and food production, but are also key for biodiversity conservation and rural livelihoods. The prospects of global change, and its impacts on these rangelands, are now being explored in the ongoing debate about the sustainable use of rangelands (e.g. Gillson et al.3). Part of this discussion has to be on how we can develop new ways of using these rangelands that are both sustainable and of value to society. It is fitting that, in going the full circle of the Swedish connection, a recent workshop was held under the auspices of the 2019 South Africa–Sweden University Forum’s (SASUF) Research and Innovation Week that focused on innovative and out-of-the-box ideas around future rangelands.